Pedagogy in Basic and Higher Education - Current Developments and Challenges 2020
DOI: 10.5772/intechopen.89513
|View full text |Cite
|
Sign up to set email alerts
|

School-University Partnership for Evidence-Driven School Improvement in Estonia

Abstract: It has been acknowledged that evidence-driven practices may lead schools to improved instructional practices, student learning, or organizational improvement; still the evidence is underused by the teachers or school leaders. This study focuses on analyzing how to strengthen the evidence-driven school improvement in school-university partnership programs. Five schools learnt over a period of one school year in collaboration with the university coaches how to collect evidence in classroom and organizational lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Unlike data, information has 'meaning, relevance and purpose by contextualizing, calculating, connecting and summarizing data' [8] (p. 482). This information can further be used as evidence: a type of information that helps assess the truth or the validity of any possible claim [19]. In Estonian, however, these terms are often used interchangeably, which may cause confusion.…”
Section: From Data To Evidence-driven School Developmentmentioning
confidence: 99%
“…Unlike data, information has 'meaning, relevance and purpose by contextualizing, calculating, connecting and summarizing data' [8] (p. 482). This information can further be used as evidence: a type of information that helps assess the truth or the validity of any possible claim [19]. In Estonian, however, these terms are often used interchangeably, which may cause confusion.…”
Section: From Data To Evidence-driven School Developmentmentioning
confidence: 99%
“…Evidence-based school improvement practices are needed to guide these interwoven processes in digitally innovative schools. Vanari et al (2020) have demonstrated that when schools are scaffolded with frameworks and tools to plan, monitor and evaluate their digital maturity (e.g. Ilomäki & Lakkala, 2018), the evidence-driven practices are more widely adopted as part of the school improvement process.…”
Section: Introductionmentioning
confidence: 99%